The flipped classroom and its influence on learning levels: a review systematic of the last 10 years in Latin America - Pino-Apablaza , Fernando (2022)
The systematic review, carried out with the PRISMA methodology, aimed to determine which are the investigations published in indexed journals, which address the issue of the flipped classroom and its relationship on the levels of learning in the field of education of the third educational level. The following two inclusion criteria were used: educational levels and indexing. And within the exclusion criteria the criteria were also two: time and geo location. The research was searched in the metasearch engines of the Scientific Electronic Library On Line SciELO, the database of SCOPUS, Google Scholar and the Network of Scientific Journals of Latin America and the Caribbean, Spain and Portugal REDALYC. To write the search equation, the Boolean operator AND was used as follows: "flipped classroom" AND "learning levels". Finally, 36 scientific investigations were identified, published in indexed scientific journals that met the inclusion and exclusion criteria.